(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes single-component sentences of the Russian language in riddle discourse within the framework of the cognitive-pragmatic approach. The purpose of the analysis is to determine the conceptual and communicative features of single-component structures. The research material was texts from the classic publication “Riddles of the Russian People” by Dmitry Nikolaevich Sadovnikov, one of the largest Russian ethnographers and collectors of folklore.